دور الانترانيت في تفعيل الاتصال الداخلي بالمؤسسة الاقتصادي - مراد براهيم; د/النوعي عبد القاد ر (جامعة عمار ثليجي الاغواط, 2023)
ملخص الدراسة : الإنترنت دورًا حيويًا في تفعيل الاتصال الداخلي في المؤسسات الاقتصادية، ويسهم في تحقيق العديد من الفوائد والتحسينات. وسوف ألخص لك بعض النقاط المهمة فيما يتعلق بدور الإنترنت في تفعيل الاتصال الداخلي في مديرية الصيانة بسوناطراك في الاغواط. يعمل الإنترنت على تبسيط وتسهيل عملية التواصل الداخلي بين الموظفين والإدارات المختلفة في مديرية الصيانة. يتيح استخدام البريد الإلكتروني والمحادثات الفورية ومنصات التعاون عبر الإنترنت إمكانية الاتصال والتبادل السريع للمعلومات والمستندات بين الأفراد والفرق بفضل الإنترنت، يمكن للموظفين الوصول إلى المعلومات والموارد اللازمة لأعمالهم بسهولة وسرعة ، يمكنهم الوصول إلى قواعد البيانات الداخلية والمواد التدريبية والأدوات والتطبيقات عبر الإنترنت، مما يسهم في زيادة الكفاءة وتحسين جودة العمل. التعاون والتنسيق: يتيح الإنترنت وسائل التواصل المختلفة، مثل البريد الإلكتروني والمنتديات والمشاركة في المستندات، التعاون الفعال بين أفراد الفرق والإدارات المختلفة في المديرية. يمكن للموظفين تنسيق الأعمال ومشاركة المعلومات والأفكار بسهولة، مما يعزز التعاون والعمل الجماعي. Summary: The internet plays a vital role in activating internal communication within economic institutions and contributes to achieving numerous benefits and improvements. Here are some important points regarding the role of the internet in activating internal communication within the Maintenance Directorate at Sonatrach in Laghouat. Simplifying communication: The internet simplifies and facilitates the process of internal communication between employees and different departments within the Maintenance Directorate. The use of email, instant messaging, and online collaboration platforms enables quick communication and exchange of information and documents among individuals and teams. Thanks to the internet, employees can access information and resources needed for their work easily and quickly. They can access internal databases, training materials, tools, and applications online, which contributes to increased efficiency and improved work quality. Collaboration and coordination: The internet enables various communication channels, such as email, forums, and document sharing, facilitating effective collaboration among team members and different departments within the Directorate. Employees can coordinate tasks and easily share information and ideas, enhancing collaboration and teamwork. In conclusion, the internet plays a vital role in activating internal communication within economic institutions. It simplifies communication, increases efficiency, and facilitates collaboration and coordination among employees and departments, ultimately contributing to improved productivity and effectiveness.
دراسة ميدانية بمديرية الصيانة بالاغواط D.M.L )سوناطراك